Model Pengelolaan Pariwisata Berbasis Masyarakat untuk Keberkelanjutan di Desa Wisata XYZ - I Wayan Suwidnyana; Ni Gst Nym Suci Murni; Ni Nyoman Sri Astuti (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
This study aims to analyze the main challenges in managing Community-Based Tourism (CBT) and develop a sustainable management model for Cemagi Tourism Village, Badung, Bali. This study uses a qualitative approach by combining primary and secondary data. Primary data were obtained through field observations, in-depth interviews, and Focus Group Discussions (FGDs), while secondary data were obtained from literature studies and related documents. The analysis was conducted using the SWOT method and qualitative descriptive methods to describe the actual conditions and opportunities for tourism village development. The results show that tourism village management still faces several challenges, particularly in the aspects of promotion and preservation. Collaboration with various stakeholders is necessary, particularly in utilizing social media as an effective promotional tool. In addition, the preservation of local nature and culture is key to sustainable tourism. The proposed management model places the village government and traditional villages as mentors, Village-Owned Enterprises (BUMDes) and Tourism Awareness Groups (Pokdarwis) as managers, and the community as active actors in every stage of development. The model refers to the POAC (Planning, Organizing, Actuating, Controlling) management theory, taking into account three aspects of sustainability. First, the economic aspect, through increasing village income, creating jobs, and equitable profit sharing through the Village-Owned Enterprise (BUMDes). Second, the socio-cultural aspect, realized through preserving cultural heritage, improving the quality of human resources through tourism training, and strengthening the role of traditional arts. Third, the environmental aspect, with a focus on preserving subak (village-owned enterprises) and green spaces, managing waste using the 3Rs (reduce, reuse, recycle), and nature conservation. Thus, sustainable tourism management requires strong collaboration, cultural preservation, and environmental awareness to ensure long-term benefits for local communities.